THE ROLE OF THE TURKMAN NATIONAL CULTURAL CENTER OF SURKHANDARYA REGION IN THE STRENGTHENING OF INTERNATIONAL RELATIONS (Scientific journal of the Fergana State University, 2023)
The purpose of the given scientific research work is to show the attention paid to the Turkmen people in the region, and to show that the same conditions have been created for representatives of different nationalities living in the country, and to interpret it correctly. In this research work, the methods of obtaining information through scientificity, objectivity, mutual comparison of sources, and brainstorming were used, and the topic was revealed based on specific facts about the issue. As a result of scientific research, the importance of Turkmen people living in the territory of the region in inter-ethnic relations, the role of national-cultural centers in the development of the oasis was revealed. The conclusion of this scientific research was that it was shown that the role of national-cultural centers is important in promoting their national customs and values. Also, in the article, people of Turkmen nationality, the activity program of the Turkmen National Center, statistics of people of Turkmen nationality in the Surkhan oasis were revealed on a scientific basis.